Mentoring Whiteness: A Critical Examination of Equity and Power in Early Childhood Education Field Placements - Warren, Melinda Alysha (Journal of Childhood Studies)

(untitled) (Canadian Association for Young Children, 2026)
Mentorship in early childhood education (ECE) field placements plays a pivotal role in shaping professional identity and pedagogical development. Yet, mentorship is not neutral nor universally experienced. Grounded in the theoretical work of Sara Ahmed and Kevin Kumashiro, this article critically examines how mentorship in Ontario ECE programs can reinforce whiteness and marginalize racialized and international preservice educators. Through an analysis of existing policy frameworks, including How Does Learning Happen? and the College of Early Childhood Educators’ Code of Ethics and Standards of Practice, and engagement with critical scholarship, three themes are explored: (1) the reproduction of white professional norms, (2) the misalignment between equity-focused policy and field placement practice, and (3) the potential for antioppressive mentorship as transformative praxis. The analysis demonstrates that mentorship often functions as a mechanism of institutional gatekeeping and exclusion. Reimagining mentorship through an antioppressive and relational lens requires sustained self-reflection, structural change, and accountability. By examining how equity is undermined through daily mentorship practices, this article calls for a critical reorientation of how mentorship is conceptualized and enacted in early learning contexts.